P‐12.5: Light Intensity Modulator Based On Electro‐hydrodynamic Instabilities in Dirchroic‐dye‐doped Liquid Crystal Cell. (26th August 2021) - Zhou, Bojun; Che, Chuncheng; Li, Yue; Wang, Chunlei; Zhai, Deshen; Wu, Yifan; Chang, Wenbo; Xiao, Yuelei; Gong, Lin; Cao, Xue; Han, Jidong; Song, Xuechao; et al.
Abstract : This paper explores the applications of dichroic‐dye‐doped liquid crystal that is set to work as broadband light intensity modulator. Taking advantage of the residual voltage formed by mobile ions and excitation of electrohydrodynamic instabilities(EHDIs) in liquid crystal cell, pulse, sinusoidal and oscillating waveforms of the transmitted light with tunable frequency are demonstrated.